Ovarian Gynandroblastoma with a Juvenile Granulosa Cell Tumor Component in a Postmenopausal Woman - Soohyun Hwang; Byoung-Gie Kim; Sang Yong Song; Hyun-Soo Kim (Diagnostics, 2020)
Ovarian gynandroblastoma (GAB) is an extremely rare sex cord-stromal tumor showing morphological evidence of both female (granulosa cell tumor) and male (Sertoli–Leydig cell tumor (SLCT)) components. Almost all GAB cases have been reported in children, adolescents, or women of reproductive age, and most of them typically have adult granulosa cell tumors as the female component. In contrast, GAB with a juvenile granulosa cell tumor (JGCT) component is a very rare condition; to the best of our knowledge, only one case of GAB with JGCT in a postmenopausal woman has been reported. In this report, we present an extremely rare case of ovarian GAB with JGCT in an elderly patient. A 65-year-old woman presented with an abdominal mass. Abdominopelvic magnetic resonance imaging revealed a large multiseptated cystic mass measuring 20 cm. No peritoneal seeding, lymph node enlargement, or hematogenous metastasis was identified. Laboratory test showed a slight elevation of serum CA 125 level (37.1 U/mL). Based on the preoperative clinical impression of ovarian cancer, she underwent a total hysterectomy with bilateral salpingo-oophorectomy. Grossly, the ovarian mass had a smooth and glistening surface without excrescences. The cut sections showed yellow-to-tan solid areas with foci of necrosis, myxoid degeneration, and hemorrhage, as well as multilocular cystic cavities filled with serosanguinous fluid. Histologically, the female component was characterized by JGCT displaying nodular growth patterns with follicle-like structures of various shapes and sizes. Most of the microcysts contained eosinophilic or basophilic secretions. The JGCT cells had indistinct cell borders, an abundant eosinophilic cytoplasm, and round-to-oval hyperchromatic nuclei with many mitotic figures. The SLCT component consisted predominantly of intermediately differentiated Sertoli cells forming lobulated solid nodules. They were arranged in cords, solid tubules, or nests, and possessed oval-to-spindle-shaped darkly stained nuclei and scant cytoplasm. In several foci, well-formed Sertoli cell tubules were loosely aggregated within areas of moderately differentiated SLCT. In summary, we described GAB in a postmenopausal woman with JGCT and SLCT as the female and male components, respectively. This is the second case of GAB with JGCT occurring in an elderly patient. Our findings can help pathologists and clinicians make accurate histological diagnoses of GAB with a JGCT component and plan an adequate treatment strategy for this rare tumor.